Pertanggungjawaban Beneficial Owner terhadap Tindak Pidana Korporasi di Bidang Pasar Modal di Tinjau dari KUHAP - Sandhi Bagus Permana (Jurnal Hukum Lex Generalis, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) has introduced a new legal paradigm by formally recognizing corporations as subjects of criminal liability. In order to enforce this substantive law, comprehensive formal legal frameworks are imperative to provide law enforcement agencies with clear guidelines and directives in prosecuting corporate entities. Furthermore, criminal offenses attributed to corporations are frequently characterized as whitecollar crimes, inherently involving highly trained individuals and seasoned professionals; this is particularly evident in capital market violations. The objective of this research is to examine the paradigms of corporate liability set forth in the 2023 Criminal Code, the 2025 Criminal Procedure Code and Law Number 4 of 2023 regarding the Development and Strengthening of the Financial Sector (UUP2SK). Employing a normative juridical research methodology, this study conducts a rigorous examination by utilizing statutory regulations, legal theories, principles and doctrines as its primary analytical framework. The findings of this study elucidate the distinct characteristics of corporate criminal liability, including the determination of who shall stand trial as the defendant in the event that a corporation is indicted for a criminal offense. Keywords: Capital Market Crime, Corporate